(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
The study was carried out to evaluate the effectiveness of different commercially available anthelmintic against gastrointestinal helminth parasites of buffaloes in Dinajpur district over a period of one year from July 2009 to June 2010. A total of 232 samples were randomly collected from buffaloes of which 199 (85.78%) were found to be positive with the help of “Modified Stoll’s Dilution Technique. Out of positive samples 40 Fasciolia infected buffaloes were selected for anthelmintic trial and 10 cases were selected for control. The anthelmintic efficacy of Triclabendazole and Nitroxynil were determined on the basis of faecal egg counts. The trial demonstrated excellent efficacy of Nitroxynil (Nitronex®, Renata Ltd.)@ 1.5 ml/ 50kg body weight against fascioliasis significantly (p<0.01 & p< 0.05) reduce the EPG on day 7 , 14 and 21 post –treatment as 54.04%, 70.68% 100% respectively and Triclabendazole (Fasinex®, Novartis Ltd.)@ 12 mg/kg body weight also significantly (p<0.01 & p< 0.05) reduce the epg on day 7 , 14 , 21 and 28 post –treatment as 53.94%, 60.04%, 83.36% and 100% respectively. Out of positive samples, 40 cases were selected randomly for anthelmintic trial against nematodiasis. The anthelmintic efficacy of Thiophanate and Levamisole on faecal egg counts of nematodiasis affected buffalo were determined. The trial demonstrated the efficacy of Thiophanate (Nemafax® Rampart power Ltd.) @ 1 gm/ 14 kg body weight against nematodiasis was significantly (p<0.01) reduces the EPG of faeces on day 7 , 14 , 21 and 28 post –treatment 52.61%, 59.28%, 72.80% and 100%respectively. The efficacy of Levamisole (Ralnex®, Novartis Ltd.) @ 7.5 mg/ kg body weight against nematodiasis was significantly (p<0.01) reduces the EPG of faeces on day 7, 14, and 21 post –treatment day 60.02%, 83.39% and 100% respectively. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (3), 448-452